2021
DOI: 10.3233/wor-205276
|View full text |Cite
|
Sign up to set email alerts
|

University professors’ mental and physical well-being during the COVID-19 pandemic and distance teaching

Abstract: BACKGROUND: Strict strategies including lockdowns and working from home were adopted worldwide during the coronavirus (COVID-19) pandemic. University professors suddenly shifted to work from home adopting distance teaching. OBJECTIVES: This study aimed to investigate Health-Related Quality of Life (HRQoL) and its associated occupational and health factors during COVID-19 among university professors. METHODS: A cross-sectional design targeted university professors of all majors in Jordan. The study self-adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 43 publications
3
25
0
1
Order By: Relevance
“…Social support has been proved to reduce the psychological and physiological consequences of stress and may enhance immune function ( Heinze et al, 2015 ; Harandi et al, 2017 ; Xu, 2019 ). Indeed, our study and several other studies ( Zhou et al, 2018 ; Almhdawi et al, 2021 ) show that higher income is a predictor of higher HRQoL. Higher income reduces financial pressure and enables high standards of living, which can contribute to better health.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Social support has been proved to reduce the psychological and physiological consequences of stress and may enhance immune function ( Heinze et al, 2015 ; Harandi et al, 2017 ; Xu, 2019 ). Indeed, our study and several other studies ( Zhou et al, 2018 ; Almhdawi et al, 2021 ) show that higher income is a predictor of higher HRQoL. Higher income reduces financial pressure and enables high standards of living, which can contribute to better health.…”
Section: Discussionsupporting
confidence: 71%
“…Common instruments assessing HRQoL include the World Health Organization Quality of Life Questionnaire (WHOQOL-100 and WHOQOL-BREF), the EuroQol 5-Dimension (EQ-5D-3L, EQ-5D-5L, and EQ-5D-Y), the Short-Form 36 (SF-36, SF-12, SF-6), the Health Utilities Index (HUI2 and HUI3), the 15-dimensional measure (15D), the Quality of Life Assessment (AQoL-8D), and the Quality of Wellbeing Scale Self-Administered Form (QWB-SA) ( Zheng et al, 2021 ). The WHOQOL-BREF, the SF-6D, and the Total Quality of Work Life (TQWL-42) instruments have been used in assessing the HRQoL of university academics in Thailand ( Sriutaisuk, 2014 ), Malaysia ( Naslina et al, 2012 ; Manaf et al, 2021 ), Brazil ( Sanchez et al, 2019 ), and Jordan ( Almhdawi et al, 2021 ). In China, the SF-36 is perhaps the most commonly adopted instrument for assessing HRQoL of university employees ( Ge et al, 2011 ; Liu et al, 2015 ; Yao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…High rates of mental health deficits and sleep problems among healthcare providers are frequently cited in the literature (Chong et al, 2004; Sassmannshausen et al, 2016). Similarly, the current COVID-19 pandemic showed high level of stress on the mental health of hospital physicians and other healthcare professionals (Almhdawi, Alazrai, et al, 2021; S. K. Brooks et al, 2020; Huang et al, 2020; Xiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Akour et al ( 2020 ) found that the professors showed moderate or high motivation about the teaching strategies adopted during the SD; however, they found a higher prevalence of signs of distress in the male audience. Almhdawi et al ( 2021 ) showed an increase in professors’ quality of life after implementing online teaching; on the other hand, there are studies (Akour et al, 2020 ; Brooks et al, 2020 ; Kotowski et al, 2022 ; Malkawi et al, 2020 ; Minihan et al, 2022 ) that report increased stress levels due to the transfer to online teaching, directly—and negatively—impacting the quality of life of this population, as well as reduced performance satisfaction for these professors.…”
Section: Discussionmentioning
confidence: 99%